Rampage Shootings and Gun Control Politicization and Policy Change in Western Europe - Hurka, Steffen (Taylor & Francis, 2017)
While the causes of rampage violence have been analysed thoroughly in diverse academic disciplines, we hardly know anything about the factors that affect their consequences for public policy. This book addresses rampage shootings in Western Europe and their conditional impact on politicization and policy change in the area of gun control. The author sets out to unravel the factors that facilitate or impede the access of gun control to the political agenda in the wake of rampage shootings and analyses why some political debates lead to profound shifts of the policy status quo, while others peter out without any legislative reactions. In so doing, the book not only contributes to the theoretical literature on crisis-induced policy making, but also provides a wealth of case-study evidence on rampage shootings as empirical phenomena.